Стан дослідження історії білорусів на півдні України у революційну добу: огляд сучасних публікацій - Новікова, Л. (Чорноморська минувшина, 2021)
В огляді сучасних українських, білоруських та польських публікацій, присвячених білорусам на півдні України та м. Одесі в 1917-1919 рр., здійснено аналіз структури дослідницької проблематики. З’ясовано, що історія білорусів у регіоні подається переважно в контексті історії білоруського національного руху та білоруського національного державотворення. Водночас було встановлено, що низка аспектів проблеми вимагає додаткового дослідження, в першу чергу це стосується біографістики, а саме діяльності в регіоні окремих лідерів білоруського національного руху. The article is devoted to the analysis of contemporary Ukrainian, Belarusian and Polish historiography of the history of Belarusians in the south of Ukraine and in Odesa and the district during the Ukrainian National-Democratic Revolution. The scientific relevance of the problem of research is associated with an insufficient level of its research in Ukrainian historiography. This aspect was chosen with taking into account the fact that during the Ukrainian National Democratic Revolution of 1917-1920 the territory of Southern Ukraine, mainly the city of Odesa and the district, due to economic ties and its political significance, became an important region for concentration of Belarusians, their trade activities, participation in political life and national state construction, etc. Of particular interest are the researches of M. Sсhavlinskiy, D. Mikhalyuk, O. Zubko. The researchers from Odesa are represented insufficiently. Researchers address such important problems as the creation of the Belarusian National Council in Odesa, the Belarusian National Commissariat and the Consulate, the activities of Belarusian national organizations. Most of the research examines the history of Belarusians in the south of Ukraine and the city of Odesa in the context of studying other problems. As a result of the study, it was found that in modern historiography – Ukrainian, Belarusian, Polish – some aspects of the history of Belarusians in the south of Ukraine, mainly in Odesa and the district, were covered for the period of 1917-1919.The researches are as special as and more general, in which events in the region are mentioned briefly in the context of a wider problem related mainly to the Belarusian national movement and the Belarusian state construction. As a rule, the investigators are limited only to mentions of personalities, or briefly characterize the Odesa period of their biographies. Further research requires the problem of interaction between the Belarusian ethnic group in the population of Odesa and in the south of Ukraine in the early XX century and Belarusian refugees during World War I, also Belarusian cultural and educational activities in the south mentioned in the research literature, etc.